Prevalence, persistence and control of Salmonella and Listeria in shrimp and shrimp products: A review - Wan Norhana, M.; Poole, S.; Deeth, H.; Dykes, Gary (Pergamon, 2010)
Shrimp are an important commodity in the international fisheries trade and there is an indication of an increase in worldwide consumption of this crustacean. Salmonella and Listeria have been isolated from shrimps and shrimp products on a regular basis since the 1980s. The continued reporting of the presence of these pathogens in fresh and frozen shrimps, and even in the lightly preserved and ready-to-eat products, indicates that the existing practices used by the manufacturers or processors are insufficient to eliminate these pathogens. This paper reviews the information available on Salmonella and Listeria in shrimp and makes recommendations on control options and avenues for future research in order to improve shrimp safety and quality. © 2009 Elsevier Ltd. All rights reserved.